The flavours of love: A cross‐cultural lexical analysis. (3rd January 2018) - Lomas, Tim
Abstract: Linguists have often remarked upon the polysemous nature of love, whereby the term encompasses a wide diversity of emotional relationships. Several typologies have been constructed to account for this diversity. However, these tend to be restricted in scope, and fail to fully represent the range of experiences signified by the term 'love' in discourse. In the interest of generating an expanded typology of love, encompassing its varied forms, an enquiry was conducted into relevant concepts found across the world's cultures, focusing on so‐called untranslatable words. Through a quasi‐systematic search of published and internet sources, 609 relevant words were identified. These were organised through a version of grounded theory into 14 categories, representing 14 different forms or 'flavours' of love. The result is an expanded theoretical treatment of love, allowing us to better appreciate the nuances of this most cherished and yet polysemous of concepts.